Algorithm of calculation and analysis of corrosive wear of side enclosures of glass furnace bath - Бекназарян, Давид Владимирович; Кошельник, Вадим Михайлович; Ларин, Алексей Александрович (Eastern-European Journal of Enterprise Technologies, 2014)
Corrosive wear of refractory materials when in contact with high-temperature melt is the main reason to stop the melting units for cold repair. In continuous fiery glass furnaces, side enclosure of melting chamber is exposed to the most widespread and intense destruction in the flux block-glass melt contact zone. Maximum corrosion rate is observed in the glass melting area, which is caused by the highest temperatures of combustion and melting products. In this regard, longitudinal section of side enclosure of the melting area was selected as the subject of the study. Using finite-element modeling, an algorithm that allows to calculate two-dimensional temperature field in the given section of refractory and insulating materials was developed. Based on the obtained data, thickness of destroyed refractory material for each nodal point of the finite element mesh on the flux block-glass melt boundary for a time period equal to one day is calculated. Furthermore, the flux block geometry is rebuilt considering the destroyed sites, and the calculation is repeated. The basis for finishing calculations is achieving a minimum flux block thickness. According to the operational data, this value is 40-50 mm. Also the analysis, confirming the appropriateness of the selected size of the finite element, used for model partitioning was conducted. Based on the algorithm, a software package, allowing to calculate temperature fields in the section of multilayer side enclosure of the melting chamber of the glass furnace, determine the service life of the enclosure, as well as to define the configuration of corrosive wear-prone sites of flux block was developed.